MEMBEDAH GAYA HIDUP HEDONIS DARI PERSPEKTIF FILSAFAT STOIKISME (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2025)
Hedonism, as an ethical doctrine that places pleasure as the highest goal in life, has undergonea significant shift in meaning in modern contexts. This article explores the phenomenon ofcontemporary hedonistic lifestyles, which are deeply rooted in consumerist and instantgratification tendencies, drifting away from the reflective values originally proposed byphilosophers such as Epicurus. Through a qualitative approach and literature review, thediscussion begins by examining the definition and classical essence of hedonism, followed bythe identification of both historical and modern forms that thrive in today’s digital culture. Thearticle highlights the link between a consumerist lifestyle and instant gratification as theprimary manifestations of modern hedonism. Social media, exhibitionist culture, andconsumerism significantly reinforce behavior centered on superficial pleasure-seeking. Behindthis, however, lie psychological vulnerabilities and fragile life values, which are analyzedthrough the lens of Stoic philosophy. Stoicism rejects reliance on external pleasure and insteadoffers an alternative view of happiness grounded in inner peace and self-control. By drawinga comparison between hedonism and Stoicism, this article argues that true happiness is notsolely derived from pleasure, but also from the depth and meaning of life experiences.Therefore, reinterpreting and critically evaluating the modern lifestyle becomes crucial so thatindividuals are not trapped in fleeting euphoria but can achieve stable and sustainable well-being.
Keywords: hedonism, modern lifestyle, Stoicism, consumerism, happiness